CD4(+) Natural Regulatory T Cells Prevent Experimental Cerebral Malaria via CTLA-4 When Expanded In Vivo - Haque, Ashraful (Public Library of Science, 2010)
Studies in malaria patients indicate that higher frequencies of peripheral blood CD4(+) Foxp3(+) CD25(+) regulatory T (Treg) cells correlate with increased blood parasitemia. This observation implies that Treg cells impair pathogen clearance and thus may be detrimental to the host during infection. In C57BL/6 mice infected with Plasmodium berghei ANKA, depletion of Foxp3(+) cells did not improve parasite control or disease outcome. In contrast, elevating frequencies of natural Treg cells in vivo using IL-2/anti-IL-2 complexes resulted in complete protection against severe disease. This protection was entirely dependent upon Foxp3(+) cells and resulted in lower parasite biomass, impaired antigen-specific CD4(+) T and CD8(+) T cell responses that would normally promote parasite tissue sequestration in this model, and reduced recruitment of conventional T cells to the brain. Furthermore, Foxp3(+) cell-mediated protection was dependent upon CTLA-4 but not IL-10. These data show that T cell-mediated parasite tissue sequestration can be reduced by regulatory T cells in a mouse model of malaria, thereby limiting malaria-induced immune pathology.